Patient Satisfaction with the Provision of Dental Treatment - Ubaidullah, Huma Tahir, Burhan Samad, Muhammad Afrasiab Khan, Moiz Ahmed Shaikh, Tahira Sadiq, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: This study’s goal is to learn how satisfied patients are with the dental department’s services at a tertiary care hospital in Islamabad, Pakistan. Study design: A cross-sectional study Place and duration of study: The study was carried out in Islamic international dental hospital, Islamabad in six months duration. Materials and methods: In a dental hospital, a descriptive cross-sectional study was conducted. The sample size was 153, the confidence level was 95%, and the margin of error was 5%. Through the use of convenience sampling, data were gathered. To gauge patients’ impressions of their satisfaction with the hospital’s availability, accessibility, and convenience of services as well as staff behaviour, a survey was undertaken. Results: The results gathered indicated that the patients were satisfied with the dentistry department’s services. Participants expressed high levels of satisfaction with the hospital’s cleanliness, doctor’s demeanour, and appointment scheduling. It was noted that several aspects, such as waiting times, were their top priorities. Conclusion: This survey demonstrates how satisfied patients are with the periodontology department at Islamic International Dental College & Hospital in terms of accessibility, availability, and convenience. A few procedures for shortening wait times and scheduling appointments still require improvement. Keywords: patient satisfaction, dental hospital, services.